Um corpo-dissertação em movimento : uma questão de aprendizagem - Santos, Esmeraldina Sobral (2013)
This work takes body from the experiences of the anthropologist Carlos Castaneda. Besides starting point for thinking about the issues related to the body, movement and learning, the works The devil Herb, A Separate Reality and Door to infinity, the author mentioned, attend here for 1) investigate reports of experience; 2) introduce some key concepts relating to learning "witchcraft" as the will. It is worth noting that our interest in the work of Castaneda, is not in the mystical questions of shamanism, even in issues relating to the field of anthropology, but on the question of learning. For Don Juan, the old Indian sorcerer and master teacher of Carlos Castaneda, the ultimate purpose of witchcraft is just learning to become a man of knowledge. Aiming to analyze the place of movement and body in the learning process, we do the following analytical course: Skinner and Piaget discuss respectively the learning of operant behavior and learning in a broad sense. We then present the thought of Francisco Varela and Bruno Latour, especially the concepts of enaction, articulated bodies and learning affectation. With Vincianne Despret discuss the emotional, physical and involuntary aspect of learning. With this conceptual overview, we aim then put in analysis the ethical-political effects of the modes of knowledge production, effects hopelessly in this body dissertation, and further effects on life. Finally, it seems, the modulations in the concepts of body movement / action, along the exposure of authors indicated, sometimes involving other elements, such as the will and perception-attention, implying variations in the form of designing learning. We realize that according to formulation and learning the nuances of movement /action and body, this implies different productions of knowledge and reality.